"Characteristics of an Ethical Product" - Mehta, Antra (2013)
This management project and research aims to look for different characteristics that people would like to see in an ethical product. The management project will be mainly looking at the ethical consumerism and the factors that affect consumption of ethical products. It will also look at the attitude behaviour gap and work towards finding ways to bridge this gap.